GENDER MODIFICATION OF FAMILY AND MARITAL RELATIONS IN THE NORTH CAUCASUS - F. F. Poshnagidi (Гуманитарные и юридические исследования)
This article examines the gender dimension of a gradual process of transformation of family relations in the North Caucasus. Excursus into the history of gender studies allows to emphasize the complexity of the problems raised. The article discusses the modification of gender relations of spouses and the entire structure of the family.